Perkuliahan Bernuansa Layanan Bimbingan Menggunakan Pembelajaran Kontekstual dan Paradigma Pedagogi Ignatian untuk Meningkatkan Sikap Penghargaan Diri dan Orang Lain (ILIN Institute Makassar, 2019)
The purpose of this study is to determine the level of effectiveness of lecture with nuances of guidance services using Contextual Teaching Learning and Ignatian Pedagogy Paradigm in Group Dynamics Course to increase self-respect and others attitudes of students. The research subjects are 36 students participating in the Group Dynamics Course. This research method is a pre-design one-group pre-test-posttest design. The research instrument used the Scale of Self-Respect and Others Attitudes totaling 25 items with a reliability value of 0.936. This study uses descriptive data analysis techniques with categorization, and t-paired sampel test. The results showed that 27.78% of students had self-respect and others in the very high category before accepting lectures increased to 55.56% after receiving lectures. In the high category, 47.22% of students are required after attending college from 58.33% before receiving college. In the category there was a decline, namely before college there were 19.44% of students became absent (0%) after attending college. The conclusion of the results of this study is that lectures with the nuances of guidance services using CTL and IPP in the Group Dynamics Course effectively increase the self-respect and and other attitudes based on the t-paired sampel test with a significance value Sig. (2-tailed) (0.001) <(0.05).